Mewujudkan Keluarga Sehat Melalui Pusat Pelayanan Kesehatan Reproduksi(PPKR) Generasi Bangkit Desa Patek Kab. Aceh Jaya - Meylissa; Diana Lestari (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
This service aims to provide services to the community, especially for reproductive health education and ways to prevent HIV Aids. This role is very important for society, especially families who have just married or who have been married for a long time. In this team, community service provides information to the people of Patek Village, Aceh Jaya Regency. This service method uses 4 stages, namely planning/planning, problem formulation accompanied by observation, counseling and evaluation. The results of this service were 54 participants who attended the event to create healthy families through the reproductive health service center and in collaboration with the health cadres at the Patek village toddler posyandu. The conclusion from the results of this counseling is that it is hoped that residents will always know about reproductive health and provide an understanding of how important it is to live a healthy and clean life to avoid the HIV Aids virus